Design of a Web-Based Lecturer Attendance Information System Using QR Codes at Muhammadiyah University of Jambi - Ikhsan, Muhammad; Helmina, Helmina (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Information technology in the world today is developing very rapidly. This development has resulted in an information and communication system that has given birth to new innovations, one of which is online attendance using QR Code. Currently, lecturers' attendance control in teaching courses is still done manually, that is, lecturers sign absences according to the lecture schedule and courses given at the academy. Where there is a problem in this case, namely that they often forget to sign the lecturer's absence which has an impact on the lecturer's teaching honorarium. Because teaching honorarium is calculated based on the absence of control. Therefore, it is hoped that the implementation of web-based attendance using QR Code will make it easier for lecturers to take absences and help academics in recording lecturers' controlled absences which will be handed over to the finance department, thereby reducing the occurrence of errors in paying lecturers' teaching honorariums. The data collection method in this research is observation, interviews, documentation and questionnaires. System design uses DFD (Data Flow Diagram), as well as system design using HTML and PHP, while for databases using MySQL.